Evaluation of Antibiotics by Disk Diffusion and Minimum Inhibitory Concentration Breakpoints in Urinary Tract Infections: Evaluation of Antibiotics for Urinary Tract Infections - Qadir, Husnain; Rehman, Muhammad Abdur; Nasir, Sadaf; Alam, Muhammad Adeel; Ibrar, Muhammad; Shuaib, Syed Luqman (Pakistan Journal of Health Sciences, 2024)
Antibiotic resistance (ABR) has made it more challenging to treat uropathogenic organisms. It is impossible to compromise antimicrobial susceptibility testing (AST), which is essential and has a significant impact on infection treatment strategies. Although labor-intensive and technically challenging for everyday laboratory use, the agar dilution technique is appropriate for monitoring and assessing novel antimicrobials. Objective: To determine the minimum inhibitory concentration (MIC), Agar dilution technique and disk diffusion as susceptibility test methodologies. Methods: This study was carried out at Khyber Girls Medical College (KGMC) Peshawar. Keeping in view the Clinical and Laboratory Standards Institute (CLSI) guidelines AST was executed. BIOMÉRIEUX® API® kits and gram staining were utilized for identification of bacteria. The disk diffusion was performed using Thermo ScientificTM OxoidTM antibiotic discs of Co-trimoxazole, Levofloxacin, Nitrofurantoin and Fosfomycin. The MIC and zone of inhibitions for disk diffusion were noted according to the CLSI protocol. Results: 158 culture positive samples were isolated out of 680 total received. Esherechia Coli (E. coli) (74.1%) being the most isolated organism. In comparison of disk diffusion and agar dilution, categorical agreement for Levofloxacin, Cotrimoxazole, Nitrofurantoin and Fosfomycin were (82.28%, 72.15 %, 87.97% and 82.28%) respectively. Kappa coefficients of (0.64, 0.43, 0.57 and 0.37) (p < 0.0001) were calculated for Levofloxacin, Co-trimoxazole, Nitrofurantoin, and Fosfomycin respectively, revealing considerable level of agreement for these antibiotics. Conclusions: It was concluded that Agar dilution is more precise than disk diffusion but being more labor intensive and technical. Disk diffusion can still produce significantly accurate results with less resource consumption.